PENERAPAN METODE COLLABORATIVE LEARNING BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA JEPANG - Erma Dewi Mayasari (Universitas Negeri Surabaya, 2020)
This type of research is classroom action research. This research was conducted on the grounds of improving the learning methods used by teachers. To improve students motivation to learn japanese in this study using 3 cycles. In each cycle have the applicatition of the same action. The result obtained in each cycle showed a positive increase in student motivation. The Final results obtained until the third cycle, each indicator increased between 5-10%. As in the indicator of being diligent in facing tasks, it increased by 5% from previous cycle. The indicator of interest in learning japanese also increased by 4% from previous cycle. And indicator of working with groups 2hen learning japanese increased 9% previously. Based onthe results obtained, it was decided that this study was terminated because the final result in cycle III had an average of 87,5%. This percentage value has fulfilled the requirements for the success indicator, namely 76%. So a study that focused on increasing students motivation to learn Japanese was decided to stop. Therefore, for the next research in addition to learning motivation, student learning outcomes should also be measured. Currently, classroom action research that has been carried out by researchers in using the collaborative larning method has succeeded in increasing students motivation to learn Japanese.